Die reaksies 40Ca([alfa,rho])43Sc EN 48Ca([alfa,rho])51Sc VIR [epsilon alfa] = 12 MeV - Froneman, S.(Sonica) (Stellenbosch : Stellenbosch University, 2012)
In die titel is die 40, 43 en 51 in superskrif.